Memnoch the devil eaudiobook - Rice, Anne (The Vampire Chronicles, 2014)
"STARTLING. . . FIENDISH. . . MEMNOCH'S TALE IS COMPELLING." —New York Daily News Like Interview With the Vampire, Memnoch has a half-maddened, fever-pitch intensity. . . Narrated by Rice's most cherished character, the vampire Lestat, Memnoch tells a tale as old as Scripture's legends and as modern as today's religious strife. —Rolling Stone "SHOCKING. . . A BRILLIANT BOOK." —St. Louis Post Dispatch "Rice has penned an ambitious close to this long-running series, as well as a classy exit for a classic horror character. . Fans will no doubt devour this last visit with Lestat." —The Washington Post Book World "MEMNOCH THE DEVIL OFFERS PASSAGES OF POETIC BRILLIANCE." —Playboy "[Memnoch] is one of Rice's most intriguing and sympathetic characters to date. . . Rice ups the ante, taking Lestat where few writers have ventured: into heaven and hell itself. She carries it off in top form." —The Seattle Times "RICHLY DESCRIPTIVE. . . A HORRIFIC TOUR OF HELL." —Kirkus Reviews (starred) A MAIN SELECTION OF THE BOOK-OF-THE-MONTH CLUB AND THE QUALITY PAPERBACK BOOK CLUB